Simulating Hydraulic Fracture Re-orientation in Heterogeneous Rocks with an Improved Discrete Element Method - He, Qingyuan; Zhu, Lei; Li, Yingchun; Li, Danqi; Zhang, Boyang (Rock mechanics and rock engineering, 2021)
Understanding the hydraulic fracture (HF) re-orientation mechanism from artificial weaknesses is critical to screen-out prevention in the petroleum industry and caveability management in the mining industry. An improved discrete element method is proposed and incorporated in the Universal Distinct Element Code (UDEC) to simulate hydraulic fracturing in heterogeneous rocks, and its reliability is validated against previous laboratory experiments. The effects of rock heterogeneity and rock strength on HF re-orientation are unveiled to fill the research gaps in the existing knowledge. The results show that the proposed UDEC T-W (Trigon-Weibull distribution) model can well simulate HF propagation in rock samples of different homogeneity degrees and yields more realistic simulation results compared with the classic extended finite element method (XFEM). The HF re-orientation process depends on the combined effect of all the influencing factors. HFs tend to be directed by perforations if hydraulic fracturing is performed in relatively heterogeneous rocks, while the differential stress is more likely to dictate the HF propagation paths if rocks become relatively homogeneous. We also find that higher rock strength weakens the impact of the differential stress and favours the control of perforations over HF propagation. Finally, recommendations are provided for effective utilization of hydraulic fracturing at the mine site.